Orientation and patching of the latent infection membrane protein encoded by Epstein-Barr virus. - Liebowitz, D (1986)
Epstein-Barr virus is known to encode three nuclear proteins and one membrane protein (LMP) in latently infected growth-transformed cells. Studies of the plasma membrane localization and orientation of LMP by protease digestion of live cells and by immunofluorescence indicated the following. (i) At least 30% of LMP is in the plasma membrane, as opposed to other cytoplasmic membranes. (ii) A small LMP domain which corresponds to a previously proposed outer reverse turn between the first two transmembrane domains is exposed on the outer cell surface (and two other proposed outer-reverse-turn domains may be exposed), whereas all or almost all of the rest of the protein is not exposed on the outer cell surface. (iii) LMP is present in patches in the cell plasma membrane.